2022
DOI: 10.1007/s00246-022-02859-3
|View full text |Cite
|
Sign up to set email alerts
|

An Interactive, Multimodal Curriculum to Teach Pediatric Cardiology to House Staff

Abstract: Pediatricians must be able to diagnose, triage, and manage infants and children with congenital heart disease. The pediatric cardiology division at the Medical University of South Carolina updated their curriculum for pediatric residents to a format supported by constructivist learning theory. The purpose of this study is to determine if shorter, interactive learning with fellow and faculty involvement improved pediatric cardiology knowledge demonstrated through test scores and resident satisfaction. A curricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…However, our results are similar to other studies, which found slight increases in objective scores for certain topics delivered using the FC format 10 . Yet the data is mixed, and some studies were unable to detect a difference in scores with either format 11–13 . Furthermore, some of the literature suggests that active learning, rather than the mode of delivery of didactics curriculum, results in improved test scores 11,14 .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…However, our results are similar to other studies, which found slight increases in objective scores for certain topics delivered using the FC format 10 . Yet the data is mixed, and some studies were unable to detect a difference in scores with either format 11–13 . Furthermore, some of the literature suggests that active learning, rather than the mode of delivery of didactics curriculum, results in improved test scores 11,14 .…”
Section: Discussionsupporting
confidence: 83%
“…10 Yet the data is mixed, and some studies were unable to detect a difference in scores with either format. [11][12][13] Furthermore, some of the literature suggests that active learning, rather than the mode of delivery of didactics curriculum, results in improved test scores. 11,14 Despite these limitations, our mode of FC delivery is unique in that it also incorporates the utilization of open-source resources, with the goal of maximizing resident efficiency in learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pediatric residents must be able to diagnose, triage, and manage infants and children with congenital heart disease [123,124]. The pediatric cardiology division at the Medical University of South Carolina updated their curriculum for pediatric residents aiming to determine if shorter lectures with more active learning with faculty and fellow participation is associated with comprehension and retention of core pediatric cardiology knowledge as demonstrated by mean test scores [124]. The results of the study showed that using an active, multimodal educational series, pediatric residents had a significant increase in mean test scores in pediatric cardiology and demonstrated good retention.…”
Section: Discussionmentioning
confidence: 99%